HUBUNGAN DUKUNGAN SOSIAL PASANGAN DENGAN KONFLIK PEKERJAAN-KELUARGA PADA IBU BEKERJA - Utami, Karina Putri; Wijaya, Yeny Duriana (Esa Unggul University, 2018)
AbstractWorking mother frequently dealing with difficult emerged from family side and working side, working mother ought to faced simultaneous occurence when compliance one role that would make more difficult to compliance the other, that condition described as work-family conflict. Work-family conflict can be reduced by social support from husband as a significant other who can provide an encouragements, advices and also assistance to do some household and childcare. This research used quantitative non-experimental method with non-probability sampling technique with snowball sampling, the samples were 58 working mothers. Partner social support scales has coefficient reliability (α) = 0.946 consists 42 items and work-family conflict (α) = 0.946 consists 31 items. This research has result significant negative correlation (sig = 0.000 dan r = -0.532) between partner social support and work-family conflict. Working mother received high level of partner social support (27.6%) and perceived work-family conflict on low level (32.8%). Partner social support provides contribution amount 28.3% to reduce work-family conflict. The dominant dimension perceived by working mother is behaviour-based conflict that is sources from work (work interference family). Keywords: partner social support, work-family conflict, working mother AbstrakIbu bekerja dihadapkan pada kendala yang muncul dari dalam keluarga maupun dari sisi pekerjaan sehingga seringkali mengalami kondisi yang simultan dalam pemenuhan satu peran yang dapat menyebabkan kesulitan untuk memenuhi tuntutan pada peran lainnya, keadaan ini yang disebut konflik pekerjaan-keluarga. Konflik pekerjaan-keluarga dapat diperkecil kemungkinannya dengan adanya dukungan sosial dari pasangan yang dapat memberikan dorongan semangat, nasehat serta dapat memberikan bantuan dalam mengerjakan tugas rumah tangga dan pengasuhan anak. Rancangan penelitian kuantitatif non-eksperimental dan teknik non-probability sampling dengan snowball sampling, dengan jumlah 58 sampel. Alat ukur dukungan sosial pasangan mempunyai koefisien reliabilitas (α) = 0,946 dengan 42 aitem dan konflik pekerjaan-keluarga (α) = 0,946 dengan 31 item.. Hasil dari penelitian ini diperoleh yaitu ada hubungan negatif signifikan (sig = 0,000 dan r = -0,532) antara dukungan sosial pasangan dan konflik pekerjaan-keluarga, dengan pengaruh sebesar 28,3%. Ibu bekerja yang mendapatkan dukungan sosial pasangan tinggi (27,6%) dan yang mengalami konflik pekerjaan-keluarga rendah (32,8%). Dimensi konflik pekerjaan-keluarga dominan adalah konflik disebabkan perilaku (work interference family). Kata kunci: dukungan sosial pasangan, konflik pekerjaan-keluarga, ibu bekerja